Pengaruh Program Corporate Sosial Responsibility CSR PT Tunas Baru Lampung Tbk Banyuasin Terhadap Kesejahteraan Masyarakat dalam Perspektif Islam - Siti Ambarwati; Armansyah Walian; Erdah Litriani (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) programs on community welfare. The research employs two variables, namely Corporate Social Responsibility as the independent variable and Community Welfare as the dependent variable. The population of this study consists of residents in Sidomulyo Village, with a sample of 97 respondents selected using a purposive sampling technique. Data were collected through questionnaires and interviews using a Likert scale that had been tested for validity and reliability. The data analysis method applied in this research is simple regression analysis. The results indicate that Corporate Social Responsibility has a positive and significant effect on community welfare. This finding suggests that well-implemented CSR programs contribute to improving the quality of life, increasing income, strengthening social relationships, and enhancing access to education and health services. Furthermore, CSR programs also support sustainable community development by empowering local communities and improving social and economic conditions. Therefore, CSR plays a strategic role in fostering long-term welfare and development within the community.